The Potential of Stigma and Gender related Local Wisdom to Conduct Region based HIV and AIDS Prevention (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Prevention of HIV and AIDS Transmission requires a program approach to solve the problem. The red zones of HIV and AIDS in Banyumas Regency are Cilongok and Purwokerto Selatan. The data from Banyumas Regency Health Office showed that until September 2015 there were 301 cases of HIV, while in 2016, there were 279 cases of HIV and AIDS cases, hence, there was a cumulative increase of cases every year. This study was conducted in August to October 2017. This study used qualitative approach with phenomenology design which was done to understand the potential of local wisdom regarding prevention of HIV and AIDS in relation with stigma and gender based on region. The data were collected through in-depth interviews on household targets in Cilongok and Purwokerto Selatan districts, represented 7 male informants and 16 female informants. The data were analysed using content analysis with narrative form. This study found that the informant did not know about the stigma, but they knew about the risk factors of HIV transmission. The informant knew about gender equality and the division of roles between husband and wife. Potential local wisdom that could be developed to prevent HIV and AIDS in the community were mutual respect, communication, mutual assistance in the division of roles in the household.